Evaluation of beneficiary satisfaction with biomedical laboratory services in Kinshasa: A case study of prescribers of biological analyses in several general referral hospitals - CHRISTIAN NGANDU KAISA; Beya Dophie Tshibuela; Pholo Dahlia Pambu; Ndaye Antoine Nkuba; Masidi Jérémie Muwonga (Orapuh Journal, 2025)
Introduction